2005
DOI: 10.1128/iai.73.2.784-794.2005
|View full text |Cite
|
Sign up to set email alerts
|

Closely Related Mycobacterial Strains Demonstrate Contrasting Levels of Efficacy as Antitumor Vaccines and Are Processed for Major Histocompatibility Complex Class I Presentation by Multiple Routes in Dendritic Cells

Abstract: Mycobacterium bovis BCG, the only vaccine available against tuberculosis (22), has also been used successfully as a vaccine against leprosy (29) and, for over 20 years, as a local immunotherapy against superficial bladder cancer (2). Mycobacterium smegmatis is a related organism which has potential advantages as a recombinant vaccine over M. bovis BCG, as it is nonpathogenic and frequently commensal in humans (36, 42). Indeed, emulsified M. smegmatis and M. bovis BCG have comparable antitumor activity in a tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 57 publications
1
19
0
Order By: Relevance
“…This observation supports the idea that intracellular bacteria are effective vaccinia vectors when a strong stimulation of the immune system is needed, such as, for example, in cancer vaccines (23). At the same time, it shows that transient encounters with infectious agents cross-reactive with self-produce profound and lasting effects on the immune system.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This observation supports the idea that intracellular bacteria are effective vaccinia vectors when a strong stimulation of the immune system is needed, such as, for example, in cancer vaccines (23). At the same time, it shows that transient encounters with infectious agents cross-reactive with self-produce profound and lasting effects on the immune system.…”
Section: Discussionsupporting
confidence: 81%
“…Moreover, its rapid clearance by the host differs from M. tuberculosis or even for the vaccine strain M. bovis bacillus Calmette-Guérin (21). Therefore, M. smegmatis has been used as vaccine vector, because it activates DCs and induces CD8-mediated immune responses (22)(23)(24)(25). Finally, killed M. smegmatis has been shown to provide the same adjuvant activity of M. tuberculosis during induction of EAE (15).…”
mentioning
confidence: 99%
“…Cheadle et al showed that M. smegmatis was better than BCG at promoting DC maturation. However, recombinant M. smegmatis expressing a CTL epitope of the ovalbumin (OVA) antigen did not protect against challenge with a tumor expressing this epitope, whereas BCG expressing the same epitope protected mice against the OVA epitope-expressing tumor (10). This absence of antitumor activity elicited by recombinant M. smegmatis was asso- ciated with poor presentation of peptides by the nonpathogenic mycobacteria to an OVA-specific T-cell line in vitro (10).…”
Section: Fig 4 Cytotoxic Activity Of Hiv-1-specific Cd8mentioning
confidence: 99%
“…Unlike other mycobacterial strains such as BCG that survive in host cells for months by inhibiting phagosome maturation, M. smegmatis is rapidly destroyed by phagolysosomal proteases in the phagosomes of infected cells (26,32,55,56). Nevertheless, M. smegmatis can induce cytokine production by macrophages better than pathogenic mycobacterial species (8,64) and can activate and induce the maturation of dendritic cells better than BCG by upregulation of major histocompatibility complex (MHC) class I and costimulatory molecules (10). M. smegmatis can also access the MHC class I pathway for presentation of mycobacterial antigens more efficiently than BCG (40).…”
mentioning
confidence: 99%
“…Nevertheless, M. smegmatis induces cytokine production by macrophages better than pathogenic mycobacterial species and can activate and induce the maturation of major histocompatibility complex (MHC) class I and costimulatory molecules (6,55). M. smegmatis also facilitates rapid uptake of expressed antigens and cross-presentation of antigens (12,35). Moreover, preexisting immunity to BCG may have only a marginal effect on the immunogenicity of recombinant M. smegmatis (9).…”
mentioning
confidence: 99%